Specific projection of displaced retinal ganglion cells upon the accessory optic system in the pigeon (Columbia livia). - Karten, J H (1977)
In the pigeon, the nucleus of the basal optic root, a component of the accessory optic system, projects directly upon the vestibulo-cerebellum. This nucleus receives a prominent projection composed of large-diameter retinal axons, known as the basal optic root. The cells of origin of this tract were identified using horseradish peroxidase (donor:hydrogen-peroxide oxidoreductase, EC 1.11.1.7) as a retrograde marker. Injections of horseradish peroxidase confined primarily to the basal optic root nucleus labeled displaced ganglion cells of the contralateral retina. Cell sizes were 18-30 micronm and the dendrites of these cells were confined to the first stratum of the inner plexiform layer. Approximately 3700 displaced ganglion cells were labeled after injections of horseradish peroxidase into basal optic root. In contrast, no displaced ganglion cells were labeled after injections of horseradish peroxidase into the optic tectum, which labeled only cells in the ganglion cell layer proper. These findings indicate that displaced ganglion cells constitute a unique population of retinal neurons that give rise to a bisynaptic pathway directed to the cerebellum via the nucleus of the basal optic root. These displaced ganglion cells may play a major role inoculomotor reflexes.